Elliptic Curve Scalar Multiplication Operation: a Survey Study - Waleed, Ayaat; Al Saffar, Najlae Falah Hameed (Journal of Kufa for Mathematics and Computer, 2023)
Scalar multiplication is the fundamental operation in the elliptic curve cryptosystem. It involves calculating the integer multiple of a specific elliptic curve point. It involves three levels: field, point, and scalar arithmetic. Scalar multiplication will be significantly more efficient overall if the final level is improved. By reducing the hamming weight or the number of operations in the scalar representation, one can raise the level of scalar arithmetic. This paper reviews some of the algorithms and techniques that improve the elliptic curve scalar multiplication in terms of the third level.